instant notes in developmental biology - Twyman, Dr Richard (India Taylor & Francis, 2000)
Coverage of the field in Instant Notes in Developmental Biology is current and focuses largely on the principles of embryonic development. It is designed to provide a clear summary of the principles of developmental biology in a compact and easily manageable structure.
Keywords: biology